Religious Moderation in School Digital Culture: Negotiating Students’ Religious Identities at SMAN 21 Palembang - Robi Darwis; Ahmad Zainuri; Muhammad Noupal (PT. Pusmedia Group Indonesia, 2026)
This study examines the negotiation of religious moderation within the digital culture of students at SMAN 21 Palembang. The presence of social media, WhatsApp groups, memes, and other forms of digital communication has created new social spaces that influence students’ religious attitudes and identity formation in multicultural schools. This study aims to analyze the process of negotiating students’ religious identities in the school’s digital space as well as the school’s strategies for strengthening religious moderation amidst majority-minority relations. This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving 12 informants comprising the school principal, Islamic Religious Education teachers, Christian Religious Education teachers, student organization advisors, Muslim students, and non-Muslim minority students. Data analysis was conducted using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and drawing conclusions. The results indicate that the school’s digital space functions not only as a communication medium but also as an arena for identity negotiation, symbolic struggle, and the reproduction of religious narratives among students. Memes, stickers, and social media interactions serve as forms of religious expression that can strengthen group solidarity while simultaneously creating the potential for exclusion of minority groups. Nevertheless, the school strives to foster an inclusive culture through dialogic interactions, multicultural activities, and the internalization of religious moderation values in both formal and informal contexts. This study concludes that religious moderation in schools is shaped through a dynamic process of social negotiation within students’ digital culture. This research contributes to the development of studies on digital religious moderation and multicultural education in Indonesian public schools.